Longitudinal evaluation of travel and health outcomes in relation to new bicycle infrastructure, Sydney, Australia. (September 2017) - Crane, Melanie; Rissel, Chris; Standen, Chris; Ellison, Adrian; Ellison, Richard; Wen, Li Ming; Greaves, Stephen
Abstract: Background: This study sought to evaluate the health and transport impacts of urban bicycle infrastructure for transport through a commuting corridor in Sydney, Australia. Methods: An online survey and seven-day travel diary collected health and travel data from intervention area residents, and residents of a control area with similar characteristics and distance from the city, at baseline (n = 846), and follow-up, four months (wave 2; n = 512) and 16 months (wave 3; n = 418) post-construction. Multilevel regression modelling was used to compare changes over time with distance from the cycleway. Results: In wave 3 24.5% of the intervention group reported using the new cycleway. Residents who started using the cycleway predominantly lived within 1 km of the cycleway (62%); however 13% of users in wave 3 lived more than 3 km from the cycleway. Frequent cycling (weekly) was strongly associated with use of the cycleway (p < 0.001), and remained consistent between waves 2 and 3 (p = 0.3). Changes in cycling frequency associated with distance from the cycleway were observed over time; specifically, those who lived 1.00–2.99 km from the cycleway increased their weekly cycling, compared with those either closer to or further from the cycleway (p = 0.08). These findings were replicated in a smaller sample of cyclists who recorded minutes/week cycling (p = 0.007). Improved social capital was observed in the intervention group over time; however, changes in physical activity and quality of life were not observed within the time period. Conclusions: Cycling participation has been decreasing in Sydney and Australia in recent years; however, urban bicycle transport infrastructure can have a positive impact on cycling, particularly urban cycling for transport, and has the potential to improve health and transport outcomes for city residents. Highlights: A natural experiment is used to evaluate the health and transport impacts of protected bicycle infrastructure for transport specifically. Cycling frequency remained constant amongst cyclists living near the cycleway and improved amongst those living on its fringe. Social capital outcomes were highest amongst community residents living in proximity to the cycleway.